High-resolution 13C NMR study of pressure effects on the main phase transition in L-alpha-dipalmitoyl phosphatidylcholine vesicles. - Jonas, J (1988)
The effects of pressure on the liquid-crystalline to gel transition in vesicles of L-alpha-dipalmitoyl phosphatidylcholine were investigated by high-resolution proton-decoupled natural-abundance 13C NMR spectroscopy. The linewidths of several 13C resonances, including the choline methyl groups, carbonyl carbons, and choline methylene groups and the palmitoyl methyl groups are reported as a function of pressure at 52.7 degrees C. These preliminary NMR experiments clearly demonstrate that high-pressure, high-resolution proton-decoupled natural-abundance 13C NMR spectra are a promising tool to study the phase-transition behavior and the dynamics of model membrane systems.